2016
DOI: 10.1177/2278533716671630
|View full text |Cite
|
Sign up to set email alerts
|

Employee Performance at Workplace: Conceptual Model and Empirical Validation

Abstract: The present study explores the concomitant areas for extending the scope of employee performance as a major domain of human resource (HR) effectiveness. We have interviewed researchers and corporate practitioners regarding their understanding of performance at workplace. On the basis of literature and feedback from academicians and industry professionals, a conceptual framework along with 42-item instrument on employee performance was proposed for empirical validation. The instrument obtained empirical views f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
245
0
28

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(348 citation statements)
references
References 58 publications
4
245
0
28
Order By: Relevance
“…The description of the work of a simple miner is to do mining individually, to prioritize quantity, not to be tied to the work of other employees, and not to prioritize the quality of work, so that the most visible here is productivity in the form of mining output. This has been supported by Pradhan and Jena's research (Pradhan and Jena, 2017) that most work performance is shown in the form of task performance.…”
Section: Discussionmentioning
confidence: 81%
“…The description of the work of a simple miner is to do mining individually, to prioritize quantity, not to be tied to the work of other employees, and not to prioritize the quality of work, so that the most visible here is productivity in the form of mining output. This has been supported by Pradhan and Jena's research (Pradhan and Jena, 2017) that most work performance is shown in the form of task performance.…”
Section: Discussionmentioning
confidence: 81%
“…When organizations foster superior citizenship behavior, they become more attractive places to work and are able to recruit, train, and retain the best people (Afsar & Badir, 2016). Pradhan and Jena (2017) suggest five dimensions used in research on OCB, namely altruism, conscientiousness, courtesy, civic virtue, and sportsmanship.…”
Section: Organization Citizenship Behaviormentioning
confidence: 99%
“…Every implementation of a task or job there is an activity to process or change the input (input) into an output (output) that has added value as a product or work result. Pradhan and Jena (2017) Classifying and classifying performance conceptually into three different dimensions, namely task performance that refers to employee skills in order to complete the main tasks of work. Contextual performance that refers to employee behavior that supports the organizational, social, and psychological environment in order to complete the main tasks of the job.…”
mentioning
confidence: 99%
“…Employee's performance is a multi-component concept and one can elaborate the procedure and area of performance, that is behavioral engagement of an expected result. The behavior describes here the action of people to full fill a task, whereas the term result and consequences situations about the results related to job behaviors of each employee (Pradhan & Jena, 2017). Job performance compares of job external attitudes that includes job duties allot as a part of task knowledge, job skills and task habits.…”
Section: Introductionmentioning
confidence: 99%